Functional and structural evaluation of the antileukaemic enzyme l-asparaginase II expressed at low temperature by different Escherichia coli strains - de Moura, Werner Alfinito Feio [UNESP]; Schultz, Leonardo [UNESP]; Breyer, Carlos Alexandre [UNESP]; de Oliveira, Ana Laura Pires [UNESP]; Tairum, Carlos Abrunhosa [UNESP]; Fernandes, Gabriella Costa [UNESP]; Toyama, Marcos Hikari [UNESP]; Pessoa-Jr, Adalberto; Monteiro, Gisele; de Oliveira, Marcos Antonio [UNESP] (Springer Nature, 2020)
Acute lymphoblastic leukaemia (ALL) affects lymphoblastic cells and is the most common neoplasm during childhood. Among the pharmaceuticals used in the treatment protocols for ALL, Asparaginase (ASNase) from Escherichia coli (EcAII) is an essential biodrug. Meanwhile, the use of EcAII in neoplastic treatments causes several side effects, such as immunological reactions, hepatotoxicity, neurotoxicity, depression, and coagulation abnormalities. Commercial EcAII is expressed as a recombinant protein, similar to novel enzymes from different organisms; in fact, EcAII is a tetrameric enzyme with high molecular weight (140 kDa), and its overexpression in recombinant systems often results in bacterial cell death or the production of aggregated or inactive EcAII protein, which is related to the formation of inclusion bodies. On the other hand, several commercial expression strains have been developed to overcome these expression issues, but no studies on a systematic evaluation of the E. coli strains aiming to express recombinant asparaginases have been performed to date. In this study, we evaluated eleven expression strains at a low temperature (16 °C) with different characteristics to determine which is the most appropriate for asparaginase expression; recombinant wild-type EcAII (rEcAII) was used as a prototype enzyme and the secondary structure content, oligomeric state, aggregation and specific activity of the enzymes were assessed. Structural analysis suggested that a correctly folded tetrameric rEcAII was obtained using ArcticExpress (DE3), a strain that co-express chaperonins, while all other strains produced poorly folded proteins. Additionally, the enzymatic assays showed high specific activity of proteins expressed by ArcticExpress (DE3) when compared to the other strains used in this work.
Keywords: Acute lymphoblastic leukemia (ALL); Escherichia coli ASNaseII (EcAII); Functional and structural evaluation; Low temperature expression; Recombinant enzyme